A Simple Method for Generating Light-induced Clusters of Transcription Factors: Effects on the Nuclear Distribution of OCT4 and on its Interactions With Chromatin - Diaz, Maria Candelaria (2025)
In recent years, a wealth of evidence revealed that many transcription-related molecules concentrate in membrane less nuclear compartments which are now recognized as relevant for transcription regulation. However, many aspects of this relationship remain unclear partly due to the experimental challenges of manipulating the distribution of transcription factors (TFs) in a controlled fashion.Here, we introduce a simple procedure to generate in live cells light-induced clusters (LICs) of TFs labeled with Janelia Fluor® probes through the HaloTag. When irradiated with the appropriate laser, the photooxidation/photobleaching of fluorescent molecules leads to the formation of a cluster which grows by incorporating other TF molecules, some through weak interactions. While the method was mostly tested with OCT4, other TFs such as SOX2 and the hormone-stimulated glucocorticoid receptor also form LICs. Relevantly, the inactive receptor in stem cells fails to form LICs suggesting that the process requires certain TF conformations and/or cellular contexts.Finally, we show that the recruitment of OCT4 to large LICs lowers its nucleoplasmic concentration and modifies both the overall distribution of the TF and its interactions with chromatin. In contrast, the generation of smaller LICs triggers the dissolution of nearby natural condensates of OCT4 but does not affect its nucleoplasmic concentration and OCT4-chromatin interactions. These results suggest that OCT4 condensates act as reservoirs, buffering variations in the nucleoplasmic concentration of this TF. This new method could be a valuable tool for exploring the relation between TFs distribution, landscape of interactions with chromatin and transcriptional output.